Montenegro, China, and the Media: A Highway to Disinformation? - Laure Deron; Thierry Pairault; Paola Pasquali (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2021)
On June 21, 2021, the French public television channel France 2 aired a report in which it was stated that Montenegro, a heavily indebted nation, was at risk of "having to cede some of its land to China" as a result of its inability to pay back a loan for the construction of a highway. According to reporters, Montenegro's Port of Bar could be annexed by China "completely legally," thanks to an "extraordinary contract" that had been "never seen before in Europe (...)." In reality, reporters erroneously presented a standard sovereign immunity waiver as evidence that China is entitled to seize land in Montenegro in the case of a payment default, reflecting their lack of understanding of normal international legal practice. Deron, Pairault, and Pasquali argue that criticism of problematic Chinese lending practices must be based on facts, not unfair and misguided denunciation.
Keywords: 330